Analisis Komparatif Ekstraksi Flavonoid dan Tanin dari Ulva lactuca Menggunakan Teknik Maserasi dan Ultrasonic-Assisted untuk Aktivitas Antibakteri - Lailatul Mubayyinah; Alvira Rizqi Rahmadia; Dinar Ayu Sekar Pawening; Lathifah Mudita; Sharyn Ciptadi Kodja; Ekwan Nova Wiratno (Jurnal Perikanan Unram, 2024)
Streptococcus agalactiae and Streptococcus iniae bacteria can cause mass mortality in farmed fish, resulting in negative production and economic impacts. The use of conventional antibiotics in the management of these diseases has led to resistance problems and environmental pollution. Ulva lactuca algae are known to contain bioactive compounds such as triterpenoids, flavonoids, and saponins that have antibacterial potential against Streptococcus. This study aims to evaluate the potential of Ulva lactuca algae extract as an alternative treatment for streptococcosis in Gourami (Osphronemus gouramy). The research method includes algae extraction using 90% ethanol, Streptococcus sp. bacterial culture, antibacterial activity test through disc diffusion method, and application of extracts to gouramy infected with bacteria. The results showed that Ulva lactuca extract at all concentrations did not show the ability to inhibit Streptococcus agalactiae bacteria. It is necessary to optimize the Ulva lactuca extraction process and its concentration to increase the effectiveness of Streptococcus agalactiae inhibition.